Deiksis Persona dalam Novel 很想很想你 [hĕn xiăng hĕn xiăng nĭ] Karya Mo Bao Fei Bao - Annisa Mardita; Amira Eza Febrian Putri; Tiksno Widyatmoko (Journal of Chinese Language and Culture Studies, 2024)
This study aims to describe the use of persona deixis in a Chinese novel entitled 很想很想你 [hĕn xiăng hĕn xiăng nĭ] 'Really Really Miss You' by Mo Bao Fei Bao. By using qualitative method and literature review approach, this research aims to describe the form of persona deixis and to describe its use in the context of the novel narration. The analysis shows that there are 4,504 uses of persona deixis in the novel. The results describe the dominance of third person deixis, especially for the character她[tā] 'she is a girl', as well as the significant use of first and second person deixis. The analysis illustrates that the variation in the use of persona deixis reflects the social dynamics, culture, and relationships between characters in the novel. This study presents an in-depth description of the role of persona deixis in narrative construction and character development in Chinese literary works. The findings provide a detailed picture of the use of persona deixis in the context of literary works and can help Chinese learners understand the concept of persona deixis more comprehensively, as well as contribute to the study of pragmatic linguistics.